PENDAMPINGAN SERTIFIKASI HALAL DAN SOSIALISASI KEWIRAUSAHAAN SOSIAL BAGI PELAKU UMKM DI DESA BRANTI RAYA KABUPATEN LAMPUNG SELATAN - Rina Loliyana; Rini Loliyani; Evi Meidasari; Nety Kumalasari; Hasbullah Hasbullah; Umar Bakti; Astrid Aprica Isabella; Sinta Merinda (Penerbit Widina, Widina Media Utama, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Branti Raya Village continue to face challenges in obtaining halal certification and have limited understanding of social entrepreneurship as a sustainable business development strategy. This community service activity aimed to enhance MSMEs' knowledge and capacity regarding the halal certification process while introducing the concept of social entrepreneurship. The program employed a participatory approach consisting of preparation, implementation, and evaluation stages, including outreach, training, mentoring, group discussions, individual consultations, and evaluation through pre-tests and post-tests. The results indicated significant improvements in participants' understanding of halal certification procedures, the use of the SiHalal application, and the principles of social entrepreneurship. A total of 85% of participants understood the stages of halal certification application, while 78% demonstrated improved understanding of social entrepreneurship. The program contributed to strengthening MSMEs' capacity and competitiveness while encouraging the development of businesses that generate not only economic value but also positive social impact within the Branti Raya Village community.ABSTRAKUsaha Mikro, Kecil, dan Menengah (UMKM) di Desa Branti Raya masih menghadapi kendala dalam memperoleh sertifikasi halal serta memiliki pemahaman yang terbatas mengenai kewirausahaan sosial sebagai strategi pengembangan usaha berkelanjutan. Penelitian ini bertujuan meningkatkan pengetahuan dan kemampuan pelaku UMKM terkait proses sertifikasi halal serta memperkenalkan konsep kewirausahaan sosial. Kegiatan dilaksanakan menggunakan pendekatan partisipatif melalui tahapan persiapan, pelaksanaan, dan evaluasi yang mencakup sosialisasi, pelatihan, pendampingan, diskusi, konsultasi, serta evaluasi menggunakan pre-test dan post-test. Hasil menunjukkan adanya peningkatan pemahaman peserta mengenai prosedur sertifikasi halal, penggunaan aplikasi SiHalal, dan konsep kewirausahaan sosial. Sebanyak 85% peserta memahami tahapan pengajuan sertifikasi halal, sedangkan 78% menunjukkan peningkatan pemahaman mengenai kewirausahaan sosial. Kegiatan ini berkontribusi meningkatkan kapasitas dan daya saing UMKM serta mendorong pengembangan usaha yang tidak hanya berorientasi pada keuntungan, tetapi juga memberikan dampak sosial bagi masyarakat.